2015
DOI: 10.1086/681302
|View full text |Cite
|
Sign up to set email alerts
|

Implications of water extraction on the low-flow hydrology and ecology of tropical savannah rivers: an appraisal for northern Australia

Abstract: Balancing the freshwater needs of humans and ecosystems is a fundamental challenge for the management of rivers worldwide. River regulation and water extraction can affect all components of the natural flow regime, yet few studies have investigated the effects on the low-flow end of the hydrograph. Low-flow periods are hydrologically distinctive and ecologically important, varying in nature among climatic zones. Tropical savannah rivers are characterized by highly seasonal and predictable flow regimes, but wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 83 publications
2
47
0
Order By: Relevance
“…This supports previous work in the Daly River, which found that under water-extraction scenarios that reduced dry season flow magnitude, the probability that barramundi abundance would be extremely low increased by almost 20% (Chan et al, 2012). Furthermore, King et al (2015) suggest that dry season water extraction may lead to a de-coupling of the relationship between wet season flow and barramundi recruitment strength, potentially increasing densitydependent competition among juveniles. The alteration of dry season flows-which are critical for maintaining habitat availability and conditions for successful spawning and recruitment of many small-bodied prey fishes-could also compound these changes to barramundi populations.…”
Section: Discussionsupporting
confidence: 89%
“…This supports previous work in the Daly River, which found that under water-extraction scenarios that reduced dry season flow magnitude, the probability that barramundi abundance would be extremely low increased by almost 20% (Chan et al, 2012). Furthermore, King et al (2015) suggest that dry season water extraction may lead to a de-coupling of the relationship between wet season flow and barramundi recruitment strength, potentially increasing densitydependent competition among juveniles. The alteration of dry season flows-which are critical for maintaining habitat availability and conditions for successful spawning and recruitment of many small-bodied prey fishes-could also compound these changes to barramundi populations.…”
Section: Discussionsupporting
confidence: 89%
“…() estimated that <1% of the total area of this region could be classified as perennial aquatic habitat. Not surprisingly, this annual wetting and drying exerts a dominant influence on the ecology of the region's rivers (King, Townsend, Douglas, & Kennard, ; Warfe et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The first is the timing when a GDE is connected to groundwater. This is likely to be important in systems with strong seasonal and other temporal ecological cues (e.g., fish reproduction and migration; King et al, ). Timing of groundwater connections may also strongly influence the biota of GDEs subject to seasonal or supraseasonal precipitation droughts, especially when groundwater connections maintain drought refuges in GDEs (Barbeta et al, ) or favour particular taxa (e.g., the amphipod Gammarus pulex in a groundwater‐fed English stream; Stubbington et al, ).…”
Section: The Five Steps Of Fergramentioning
confidence: 99%
“…Again, there are some major challenges to be considered when testing hypotheses about different GDEs' ecological responses to groundwater regime alteration. First, GDEs in the landscape are often affected by other stressors such as surface‐water regime alteration (e.g., King et al, ) and land uses such as grazing (Powell et al, ). Disentangling these effects from groundwater regime alteration is difficult but data on changes in surface water and land use can be incorporated into models of GDE responses (e.g., Korbel & Hose, ) to help establish potential sources of variance.…”
Section: The Five Steps Of Fergramentioning
confidence: 99%